Reservoir heterogeneity of an Eocene mixed siliciclastic-carbonate succession, northern Pannonian Basin. (January 2023) - Körmös, Sándor; Varga, Andrea; Raucsik, Béla; Lukoczki, Georgina; Radovics, Balázs Géza; Papp, Nikoletta; Futó, István; Schubert, Félix
Abstract: The quality of any reservoir is strongly controlled by diagenetic processes, especially of those that are comprised of mixed siliciclastic-carbonate sequences. An Eocene mixed siliciclastic-carbonate sequence forms reservoirs with diverse reservoir quality in the Hungarian Palaeogene Basin, which is found within the Pannonian Basin. Late Eocene transgression established extensive shallow-marine depositional environments strongly controlling the early diagenetic processes. Drill cores and cuttings were selected from several boreholes, representing a wide range of lithofacies to reveal the cause for reservoir heterogeneity. Petrographic, stable isotope and fluid inclusion analyses were performed to identify the diagenetic processes that controlled the porosity evolution of the reservoir, The early diagenetic calcite neomorphism caused lateral homogeneity, whereas the early meteoric water incursion enhanced reservoir properties via the development of dissolution pores, which in turn resulted in vertical reservoir heterogeneity. The deterioration of porosity started in the eogenetic realm by kaolinite formation and continued during mesodiagenesis as burial calcite, quartz, dolomite and minor illite cement precipitated in remaining pore spaces. Petrographic evidence, such as kaolinite transformation into dickite and fluid inclusion homogenisation temperatures highlight the role of temperature increase with burial, the effect of changing fluid chemistry during the evolution of the basin is documented by the chemical zonation of dolomite, the variation in salinities of the fluids enclosed fluid inclusions, as well as recurrent and prolonged periods of cementation with calcite, quartz and dolomite. Mesogenetic processes were accompanied by hydrocarbon emplacement and the formation of late-stage pyrite. The propagation and cementation of faults first contributed to increase and later to reduce fluid flow, respectively. These steps collectively resulted in a heterogeneous reservoir, characteristic of the Eocene sequence in the Hungarian Palaeogene Basin. Highlights: Shallow-marine depositional environment controls the eogenetic processes. Water chemistry characterises the evolution of pore fluids. Dissolution-precipitation processes serve vital role of reservoir quality enhancement. Burial depth and temperature have a critical role on the source mineralizing fluid. Hydrocarbons migrated together with basinal brines.